Introducing novel light management to design a hybrid high concentration photovoltaic/water splitting system - Videira,JJH; Barnham,KWJ; Hankin,A; Connolly,JP; Leak,M; Johnson,J; Kelsall,GH; Kennedy,K; Roberts,JS; Cowan,AJ; Chatten,AJ (IEEE, 2015)
We present a novel way to utilize high-concentrationphotovoltaic (HCPV) radiative losses and diffuse light, otherwiseunused in conventional HCPV systems, to power an ImperialCollege designed photoelectrochemical reactor (PECR) producingH2 fuel through water splitting. A high efficiency photovoltaic(HEPV) is embedded inside a Luminescent Solar Concentrator(LSC). Edge emission from the radiative recombination lossmechanism in the HEPV is guided within the LSC to the PECRphotocathode, whilst the LSC emitted light is guided to thephotoanode. The photon streams can be independently optimisedin intensity and wavelength. We demonstrate how photon streamswith balanced intensity can be achieved.